Prognosis of Children with Cerebral Palsy with and Without Therapy - Mardiati, Sri; Nasution, Mukri P. (Syntax Corporation, 2026)
Cerebral palsy (CP) is one of the most common neurological disorders in children, characterized by impairments in movement, posture, and coordination. Although CP is non-progressive and cannot be cured, its prognosis largely depends on early intervention and access to appropriate therapy. This study aims to compare the prognosis of children with CP who receive therapy and those who do not. The research employed a literature review method by analyzing scientific articles from reputable databases such as PubMed, Scopus, and Google Scholar published between 2015 and 2025. A descriptive-analytical approach was used to synthesize findings related to motor ability, independence, communication, quality of life, and secondary complications. The results indicate that children who undergo therapy, including physiotherapy, occupational therapy, and speech therapy, demonstrate significant improvements in motor skills, independence in daily activities, communication abilities, and overall quality of life. In contrast, children without therapy experience more severe developmental delays, greater dependence on caregivers, limited social participation, and higher risks of musculoskeletal complications. The discussion highlights that therapy not only enhances physical function but also supports social integration and psychological well-being. In conclusion, early and comprehensive therapeutic intervention plays a crucial role in improving the prognosis of children with CP and should be prioritized in healthcare systems.